Single‐Molecule Electrical Detection with Real‐Time Label‐Free Capability and Ultrasensitivity. Issue 5 (12th April 2017) - Gu, Chunhui; Jia, Chuancheng; Guo, Xuefeng
Abstract : Single‐molecule detection based on electricity can realize direct, real‐time, and label‐free monitoring of the dynamic processes of either chemical reactions or biological functions at the single‐molecule/single‐event level. This provides a fascinating platform to probe detailed information of chemical and biological reactions, including intermediates/transient states and stochastic processes that are usually hidden in ensemble‐averaged experiments, which is of crucial importance to chemical, biological, and medical sciences. Here, the focus is on a valuable survey of the state‐of‐art progress in single‐molecule dynamics studies that are based on electrical nanocircuits formed from one‐dimensional nanoarchitectures and molecular‐tunneling junctions. Further interesting applications, useful statistical‐analysis methods, and future promising directions toward the study of chemical‐reaction dynamics and biomolecular activities are also discussed. Abstract : The state‐of‐the‐art advances in single‐molecule detection studies that are based on electrical nanocircuits formed from one‐dimensional nanoarchitectures and molecular tunneling junctions are surveyed. Further interesting applications, useful statistical‐analysis methods, and future promising directions toward the study of chemical‐reaction dynamics and biomolecular activities are also discussed.